2011
DOI: 10.1177/1087054710392538
|View full text |Cite
|
Sign up to set email alerts
|

The Positive Illusory Bias

Abstract: College students with ADHD demonstrate self-evaluations that appear to reflect the positive illusory bias and that may be related to their academic functioning in the college setting and willingness to receive treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 41 publications
2
19
0
Order By: Relevance
“…Important for the current discussion, the extent to which any childhood positive illusory biases persist into adulthood is unclear. Evidence of PIB in the global judgments of adults diagnosed with ADHD has been limited to perceptions of driving ability (Knouse, Bagwell, Barkley, & Murphy, 2005; Prevatt et al, 2012). In other major domains, as children with ADHD grow up and experience repeated failures and negative feedback, they may “get the message” and be less likely to espouse over-inflated global self-perceptions.…”
Section: Overly Positive Thoughts In Adhd: What Do We Know?mentioning
confidence: 99%
“…Important for the current discussion, the extent to which any childhood positive illusory biases persist into adulthood is unclear. Evidence of PIB in the global judgments of adults diagnosed with ADHD has been limited to perceptions of driving ability (Knouse, Bagwell, Barkley, & Murphy, 2005; Prevatt et al, 2012). In other major domains, as children with ADHD grow up and experience repeated failures and negative feedback, they may “get the message” and be less likely to espouse over-inflated global self-perceptions.…”
Section: Overly Positive Thoughts In Adhd: What Do We Know?mentioning
confidence: 99%
“…This issue has been repeatedly described in the clinical literature on adult ADHD (Ramsay & Rostain, 2008; Sprich, Knouse, Cooper-Vince, Burbridge, & Safren, 2010; Zylowska, 2012) and the issue of bias in the cognitions of some children with ADHD—the positive illusory bias —has also been studied extensively (see Owens, Goldfine, Evangelista, Hoza, & Kaiser, 2007 for a review). Evidence for these biases and their effects in adults with the disorder is compelling, but more limited (Golden, Owens, Evangelista, & Micheli, 2006; Knouse, Bagwell, Barkley, & Murphy, 2005; Lui, Johnston, Lee, & Lee-Flynn, 2013; Prevatt et al, 2012). …”
mentioning
confidence: 99%
“…Several investigators have found a positive relationship between ADHD and substance use or SUDs (Frodl, 2010; Katusic et al, 2005; Barbaresi et al, 2013; Upadhyaya et al, 2005; Baker, Prevatt, & Proctor, 2012). Other investigators have considered the role of CD in the association of ADHD with substance use (Charach, Yeung, Climans, & Lillie, 2011; Flory & Lynam, 2005; Harty, 2012; Rooney, Chronis-Tuscano, & Yoon, 2012; Ross, 2008).…”
Section: Introductionmentioning
confidence: 99%